2017
DOI: 10.1007/s00702-017-1784-x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the reduced pteridine contents in the cerebrospinal fluids of LRRK2 mutation carriers and patients with Parkinson’s disease

Abstract: Tetrahydrobiopterin (BH4) is a cofactor for tyrosine hydroxylase that is essential for the biosynthesis of dopamine. Parkinson's disease (PD) is characterized by a progressive degeneration of nigrostriatal dopaminergic neurons, and biomarkers reflecting the degree of neurodegeneration are important not only for basic research but also for clinical diagnosis and the treatment of the disease. Although the total neopterin and biopterin levels in the cerebrospinal fluids (CSF) of the patients with PD were reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Biopterin was reported to be higher in LRRK2 PD than in sPD patients [81], and in an earlier study by the same investigators total biopterin was reported to be higher in LRRK2 PD [80]. (No results were presented in the latter study for the individual components of total biopterin.)…”
Section: Comparison Of Csf Analyte Concentrations Between Lrrk2 Pd Anmentioning
confidence: 79%
See 4 more Smart Citations
“…Biopterin was reported to be higher in LRRK2 PD than in sPD patients [81], and in an earlier study by the same investigators total biopterin was reported to be higher in LRRK2 PD [80]. (No results were presented in the latter study for the individual components of total biopterin.)…”
Section: Comparison Of Csf Analyte Concentrations Between Lrrk2 Pd Anmentioning
confidence: 79%
“…It was unclear if some of the samples were used in both studies. Conversely, although the studies on pteridines by Koshiba et al [80] and Ichinose et al [81] were both performed at the Tokyo Institute of Technology, different samples were used in the two studies. Koshiba et al used samples from carriers of the I2020T LRRK2 mutation, while Ichinose et al used carriers of the G2019S or N1437H LRRK2 mutations.)…”
Section: Csf Studies In Carriers Of Pd-associated Lrrk2 Mutations: Anmentioning
confidence: 99%
See 3 more Smart Citations